KESEHATAN PERBANKAN NASIONAL SELAMA PANDEMI COVID 19 TERHADAP NILAI PERUSAHAAN MELALUI KINERJA KEUANGAN - A.A Pt. Agung Mirah Purnama Sari; Ni Made Suindari; I Nyoman Sutapa (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2023)
This study aims to determine and analyze the Health of National Banking during the Covid-19 Pandemic on Firm Value through Financial Performance with the observation year 2018 to 2020. National banking conditions are analyzed using the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) method. The reason for choosing the banking sector in this study is because researchers want to know the impact of the Covid-19 pandemic on the banking sector and its effect on the economy of the Indonesian people. The sampling technique uses Probability Sampling type Simple Random Sampling. Meanwhile, the sampling used the Slovin Formula so that a sample of 32 companies with 96 observations was obtained. This study used 19 hypotheses. Our findings generally show that the average national bank is still in good health despite being in extraordinary conditions like the current pandemic. This is due to the consistency of other professions such as civil servants or MSME actors in fulfilling their obligations to banks so that they can support and anticipate credit problems that may arise in national banks. The results of the hypothesis test showed that only four (4) hypotheses were accepted, they are H1a, H3, H4, and H9. The results of the F test show that 71% of the firm value is influenced by Risk Profile, Good Corporate Governance, Earnings, Capital and Financial Performance.